THE DETERMINAN CARBON EMISSION DISCLOSURE PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA - -, Lilik Nurhidayah; Novianty, Nadya; Yanti, Sari; Yusri, Yusri (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2024)
company to measure, acknowledge, record, present and disclose carbon emissions. High levels emissions released companies are not commensurate with the disclosures they make, evidenced the low level carbon emission disclosures contained in sustainability reports. Companies should disclose carbon emissions in annual reports or sustainability reports. However, reporting carbonemissions in Indonesia still voluntary (voluntary disclosure). This research aims to determine the effect of growth, leverage and proper rating on carbon emission disclosure. This type of research uses associative research with a quantitative approach, with population of energy sector companies listed on the Indonesia Stock Exchange for 2020 -2022 period. The sampling technique used was purposive sampling, so sample of 16 companies was obtained. The data analysis technique uses partial least squares (PLS). Based on hypothesis testing, H1 has a p-value of 0.592 > 0.05 and a t-statistic value of 0.536 < 1.96, so growth has no effect on carbon emission disclosure. H2 has a p-value of 0.029 < 0.05 and a t-statistic value of 2,185 > 1.96, so leverage has a significant effect on carbon emission disclosure. H3 has a p-value of 0.000 < 0.05 and a t-statistic value of 4,149 > 1.96, so proper rating has a significant effect on carbon emission disclosure. Growth has no effect on carbon emission disclosure. Leverage and proper rating influence carbon emission disclosure.